Budgeting in Georgia - Kraan, Dirk-Jan (OECD Publishing, 2006)
Following the Rose Revolution of November 2003, the government of Georgia has undertaken large reform initiatives in the area of fiscal policy. These efforts have focused on taxation, tax administration, and the budget process, including cash and debt management. A new budget system law became effective in January 2004, establishing a comprehensive framework for the functions and responsibilities of the Ministry of Finance and the spending agencies via a two-stage prioritisation process guided by the annual "Basic Data and Directions" document